Transaction authentication using complementary colors. Issue 48 (February 2015) - Maeng, YoungJae; Mohaisen, Aziz; Lee, Mun-Kyu; Nyang, DaeHun
Abstract: In this paper, we introduce a transaction authentication solution that provides compatibility with any banking transactions. Our solution is based on a novel visual cryptographic scheme that supports multiple uses of a single static share, unlike existing techniques in the literature of visual cryptography. To support multiple uses, we utilize complementary colors in the subtractive color mixing model. In our solution, a user is asked to overlap an issued visual cryptography card on an encrypted image that is rendered on a screen to check transaction information and transaction authentication number. We analyze the security of our scheme against various attacks and show its effectiveness using a usability study.